Analisis Efektivitas Penyuluhan, Pelatihan Penggunaan Alat Pemadam, dan Simulasi Kebakaran pada UMKM Keripik Tempe di Jatiyoso, Karanganyar - Jordan Syah Gustav; Muhammad Alfan Alfian; Resantya Adista Maharani; Dwi Irma Amalia Husna; Rillia Rully Adisty; Renata Amara Ginesti; Aisyah Rani Sholichah; Shinta Nur Fitri; Ribby Nafian Akbar; Arsheila Sarah; Cheren Nabila Honesty Kusuma; Fahreza Wisnu Mahendra; Muhamad Efendi Kurniawan (Jurnal Sains dan Kesehatan, 2024)
According to the National Fire Protection Association (NFPA), fire caused by an oxidation process that involved fire triangle elements. The fire triangle elements consist of fuel, oxygen, and heat. Informal industry, such as UMKM, facing a high risk because of fund limitation which hinder risk analysis and post-disaster recovery, moreover lack of regulation and adequate protection measures such as fire protection systems. To decrease that risk, a fire disaster mitigation program is needed, including outreach, training about how to use a fire extinguisher, and fire simulation. This program aims to increase the knowledge and preparedness of workers in facing potential fire hazards so that the risk can be minimized and the losses can be reduced. This research using a pre-experimental design method approached by one group pretest-posttest design. According to pre-test and post-test results by the workers, there was a 9.4% increase in knowledge. It evidenced by the result of the Wilcoxon Signed Ranks Test which showed a P-value of 0.003 (p ≤ 0,05), which means there is a significant difference between the pre-test and post-test result.